Pemanfatan Kearifan Lokal Kayu Melimpah untuk Pembuatan Rumah Burung Hantu (RUBUHA) sebagai Pengendali Hama Tikus di Desa Klempun - Shofa Robbani; Benny Widya Priadana; Nazilatul Mubarokah; Cholda Najmanal Hadro (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
Klempun Village in Bojonegoro Regency relies on rice farming for income but struggles with severe infestations of rice field rats (Rattus argentiventer), which diminish yields and threaten crop failure. Conventional controls—such as chemical pesticides, electric shocks, and plastic fences—prove ineffective and pose significant health, safety, and environmental risks. To address this, the community harnesses local wisdom by constructing Owl Houses (RUBUHA) from abundant forest wood. These structures shelter barn owls (Tyto alba), natural rat predators that hunt nocturnally. Monitoring shows all RUBUHAs are occupied by owls, leading to a 30% drop in rat populations and a 60% reduction in crop damage. Consequently, rice yields have risen by 60%, and reliance on chemical pesticides has sharply declined. Beyond pest control, the initiative fosters wildlife conservation awareness and promotes ecological balance. RUBUHA thus emerges as an effective, sustainable strategy that leverages natural resources and biodiversity to enhance agricultural productivity and environmental health.